2011
DOI: 10.2478/s11535-011-0068-y
|View full text |Cite
|
Sign up to set email alerts
|

Inducing stem cell differentiation using low intensity laser irradiation: a possible novel therapeutic intervention

Abstract: Developments in adult stem cell (ASC) potentiation have contributed to excitement in the field of stem cell-based therapy. The use of ASCs not only increases therapeutic treatment possibilities but successful use of multipotent cells for gene therapy has been demonstrated in animal models [1]. Concurrent ability of stem cells (SCs) to either contribute to disease development, as identified in cancer stem cells (CSCs), or to replace diseased tissue by induced differentiation using selected growth factors, has h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 23 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…33 Biphasic dose and wavelength-related cellular response to LILI treatment LILI, also known as photobiomodulation, is a non-thermal and non-toxic phototherapy that uses coherent monochromatic low-intensity light, usually corresponding to the visible red (400-720 nm) and the near-infrared (NIR; 700-1000 nm) range of the light spectrum to induce photobiological processes at the cellular level. 34 The clinical use of LILI has so far shown no side effects in patients, making it a promising therapeutic approach in a wide range of clinical applications. 8 In the past decades, the medical application of LILI has been focused on its non-invasive biostimulatory effect.…”
Section: Cscsmentioning
confidence: 99%
“…33 Biphasic dose and wavelength-related cellular response to LILI treatment LILI, also known as photobiomodulation, is a non-thermal and non-toxic phototherapy that uses coherent monochromatic low-intensity light, usually corresponding to the visible red (400-720 nm) and the near-infrared (NIR; 700-1000 nm) range of the light spectrum to induce photobiological processes at the cellular level. 34 The clinical use of LILI has so far shown no side effects in patients, making it a promising therapeutic approach in a wide range of clinical applications. 8 In the past decades, the medical application of LILI has been focused on its non-invasive biostimulatory effect.…”
Section: Cscsmentioning
confidence: 99%
“…Moreover, a research study reported that intra‐articular injection of ADSCs and laser irradiation prevented knee joint degeneration with induced osteoarthritis [14]. Application of photobiomodulation on the bone marrow to stimulate patient's stem cells and to induce regeneration of damaged tissue is one of the most recent approaches [15,16]. Another study used a 660 nm diode laser on damaged skeletal muscle in rats, reported positive effects and an increase in the muscle regeneration process itself [17].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the hypothesis supporting the possible curative effect of laser treatment has also been questioned. However, the beneficial effects of LILI using specific light parameters in the treatment of cancer and other medical conditions have been revealed [17]. The use of LILI alone with the aim to eradicate cancer cells has still not yield convincing results.…”
Section: Resultsmentioning
confidence: 99%
“…These photobiological responses to LILI don't induce any significate elevation in temperature and highly depends on factors such as the intensity and wavelength of light applied, and the type of cell. Hence, LILI can be defined as a non-thermal photo-biomodulation technique using optical waves that usually correspond to the visible red or near-infrared (NIR) light and low fluencies to induce photobiological process at the cellular level [17,18].…”
Section: Introductionmentioning
confidence: 99%